Crisis prevention and prosperity management for the world economy - Bryant, Ralph C., 1938- (Bryant, Ralph C., 1938- Turbulent waters., 2004)
Bryant, a senior fellow in the economic studies program at the Brookings Institution, examines supranational surveillance and lending intermediation as key elements of the reform of the international financial system. He argues that national governments and international organizations need to upgrade their collective efforts at financial crisis pre.